Controle e autonomia nas gestões Kirchner e Fernández de Kirchner (2003-2011): a Argentina na construção do Conselho de Defesa Sul-Americano - Pereira, Matheus de Oliveira [UNESP] (2016)
The dissertation deals with Argentina's foreign and defense policies between 2003 and 2011, analyzing the meaning of country's participation in the construction of the Council of South American Defense. We worked with the hypothesis that Argentina's adherence and action in the CDS can be understood in light of the attention to a set of the country's interests, both from an internal viewpoint and internationally. The main argument can be summarized in three faces: 1) the setting of civil control and international cooperation in the practice of defense policy; 2) a diplomatic action driven in search for higher margins of autonomy, interpreted through a specific lens; 3) the particular logic of Argentine-Brazilian relations. An additional propose of interpretation is offered, considering the interest of Argentinian government in exercise of a leadership based on the regionalization of a set of normative definitions in the defense field. In this work, we adopt an approach that combines history and conjuncture, based on literature review and empirical research from primary sources.